The impact of NHS based primary care complementary therapy services on health outcomes and NHS costs: a review of service audits and evaluations - Wye Lesley (BMC Complementary and Alternative Medicine, 2009)
Abstract Background The aim of this study was to review evaluations and audits of primary care complementary therapy services to determine the impact of these services on improving health outcomes and reducing NHS costs. Our intention is to help service users, service providers, clinicians and NHS commissioners make informed decisions about the potential of NHS based complementary therapy services. Methods We searched for published and unpublished studies of NHS based primary care complementary therapy services located in England and Wales from November 2003 to April 2008. We identified the type of information included in each document and extracted comparable data on health outcomes and NHS costs (e.g. prescriptions and GP consultations). Results Twenty-one documents for 14 services met our inclusion criteria. Overall, the quality of the studies was poor, so few conclusions can be made. One controlled and eleven uncontrolled studies using SF36 or MYMOP indicated that primary care complementary therapy services had moderate to strong impact on health status scores. Data on the impact of primary care complementary therapy services on NHS costs were scarcer and inconclusive. One controlled study of a medical osteopathy service found that service users did not decrease their use of NHS resources. Conclusion To improve the quality of evaluations, we urge those evaluating complementary therapy services to use standardised health outcome tools, calculate confidence intervals and collect NHS cost data from GP medical records. Further discussion is needed on ways to standardise the collection and reporting of NHS cost data in primary care complementary therapy services evaluations.